Subgrade Reaction Characteristics to the Anchor Pile of a Sheet Pile Quay Wall - Miyashita, Kenichiro; Nagao, Takashi (Engineering, Technology & Applied Science Research, 2024)
The Conventional Design Method (CDM) for anchored sheet pile quay walls cannot accurately calculate the anchor pile deformation, partly because it does not properly consider the subgrade reaction. This study aims to clarify the subgrade reaction characteristics of the anchor pile using finite element analysis. The CDM assumes that passive failure occurs at the front of the anchor pile. On the contrary, this study shows that the active failure region generated from the back of the sheet pile wall expands to the periphery of the anchor pile and the passive failure region is not generated at its front. Thus, the subgrade reaction to the anchor pile is found to be smaller than the CDM assumption. The CDM also neglects the subgrade reaction in parts shallower than the tie-rod mounting height in the pile front. This study clarifies that the subgrade reaction in this part greatly contributes to the deformation resistance of the pile. Consequently, the subgrade reaction in the shallower range than the tie-rod mounting height is greater than or equal to that in the deeper range. Furthermore, the subgrade reaction has a lower upper limit when acting on the anchor pile than when acting on a horizontally stratified ground, and the difference between these limits widens as the reference earthquake strengthens.